Interactive multicriteria decision support system for spatial planning analysis - Alçada-Almeida, L. (2013)
This paper builds upon previous work entailing, in a first stage, the development of a geographic information system based environmental modelling approach and, in a second stage, the development of a stand-alone, more generic integrated spatial decision support system. The latter system was designed to address general spatial decision problems in a way that enables interactive definition of mathematical models, the spatial entities involved and their attributes. This manuscript focuses primarily on a further development to implement a multicriteria modelling framework supporting sophisticated evaluation and comparison of hypothetical alternative scenarios in the context of spatial decision problems. Typically several conflicting and generally incommensurable criteria are involved, which derive from the multidimensional nature of most of the decision problems. In such circumstances, multicriteria techniques are recommended to be used in the analysis process. Overall, at the very beginning, the decision maker is not fully aware of the whole problem in hand and hence an effective learning process needs to be undertaken. Operating interactively with the methods above, either simultaneously or following a given sequence, the decision maker may become effectively acquainted with the whole problem by investigating possible coherences among results obtained and also by analysing sensitivity of variations in input data.